Enhanced On the Job Training Internship Program for Bachelor of Science in Electrical Engineering Students - Aljon G. Martin; Deejay F. Magpayo; Jerald Jay Dela Pena; Rainer Charles M. Saddi; Alma L. Tangcuangco; Rhoderick Favorito (ASEAN Journal of Science and Engineering Education, 2023)
Following the University’s mission of providing time and cost-effective training programs in different areas, On the Job Training (OJT) is an internship program undergone by qualified students as part of their requirements before graduating. This study aimed to identify the issues concerning OJT and provide recommendations to enhance the OJT Program. Bachelor of science in electrical engineering (BSEE) students, student internship program of the Philippines (SIPP) coordinators, and potential host training establishments (HTEs) were the selected respondents of this study since they were the ones involved in the phenomena, they were gathered through stratified random sampling here they are specifically identified from a population as strata. Preliminary findings indicated various guidelines and data, addressing the enhancement of OJT Programs in terms of rules and guidelines, Time, and Schedule, Potential HTEs, and SIPP relations. Further, this study would recommend how to enhance the OJT Program for BSEE students.